The IgA Isotype of Anti-β2 Glycoprotein I Antibodies Recognizes Epitopes in Domains 3, 4, and 5 That Are Located in a Lateral Zone of the Molecule (L-Shaped) - Serrano, Manuel; Martinez-Flores, Jose Angel; Norman, Gary L.; Naranjo, Laura; Morales, Jose Maria; Serrano, Antonio (Frontiers in Immunology, 2019)
Background: Antiphospholipid syndrome (APS) is characterized by thrombosis and/or pregnancy morbidity with presence of anti-phospholipid antibodies (aPL). The APS classification criteria only consider the aPL of IgG/IgM isotype, however testing of aPL of IgA isotype is recommended when APS is suspected and consensus aPL are negative. IgA anti-β2GP1 has been clearly related with occurrence of thrombotic events. Antibodies aβ2GP1 of IgG/M isotypes recognize an epitope in Domain 1 (R39-G43), the epitopes that recognize IgA aβ2GP1 antibodies are not well identified. Aim: To determine the zones of β2GP1 recognized by antibodies of IgA isotype from patients with APS symptomatology and positive for IgA aβ2GP1. Methods: IgA antibodies to Domain-1(D1) and Domain-4/5(D4/5) of β2GP1 (ELISA) and epitope mapping on oligopeptide arrays of β2GP1 were evaluated in sera from a group of 93 patients with at least one thrombotic and with isolated positivity for IgA anti-β2GP1 antibodies (negative for other aPL). Results: A total of 47 patients (50.5%) were positive for anti-D4/5 and 23(25%) were positive for anti-D1. When peptide arrays were analyzed, three zones of β2GP1 reactivity were identified for more than 50% of patients. The center of these zones corresponds to amino acids 140(D3), 204(D4) and 264(D5). The peptides recognized on D3 and D4 contain amino acid sequences sharing high homology with proteins of microorganism that were previously related with a possible APS infectious aetiology. In the three-dimensional structure of β2GP1, the three peptides, as the R39-G43 epitope, are located on the right side of the molecule (L-shape). The left side (J-shape) does not bind the antibodies. Conclusions: Patients with thrombotic APS clinical-criteria, and isolated IgA anti-β2GP1 positivity appear to preferentially bind, not to the D1 or D4/5 domains of β2GP1, but rather to three sites in D3, D4 and D5. The sites on D3 and D4 were previously described as the target identified by human monoclonal antibodies derived from patients that were capable of inducing APS in animal models. The localization of these epitopes opens a new route to explore to increase understanding of the patholophysiology of the APS and to propose new alternatives and therapeutic targets.